Procurement Risk Management and Contract Performance in Local Governments: A Case of Mbale District - Joan Akajo (Uganda Christian University, 2024)
The study investigated procurement risk management and contract performance in local government, focusing on Mbale District. It aimed to assess the effects of supplier selection, contract management, and financial stability on contract performance. Utilizing a descriptive research design, the study sampled 45 out of 51 respondents from various departments including PDU staff, contract committee members, accountants, cashiers, health officers, stakeholders, and auditors. The results indicated that supplier selection had a strong positive correlation of 75% with contract performance, while contract management was correlated at 70%. Financial stability showed the highest correlation of 80% with contract performance. The study concluded that improving supplier selection processes, enhancing contract management practices, and ensuring financial stability are crucial for optimizing contract performance. Recommendations were made to address these areas to achieve better outcomes in procurement and contract management.